2021
DOI: 10.1101/2021.03.26.21254327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospective SARS-CoV-2 cohort study among general practitioners during the second COVID-19 wave in Flanders, Belgium

Abstract: Primary health care providers (PHCPs), especially general practitioners (GPs) are essential to organise health care efficiently. During the COVID-19 pandemic, they also keep the pressure off hospitals. PHCPs are assumed to be at high risk of a COVID-19 infection, as they are exposed to a large portion of the population (usually with less personal protective equipment than other frontline health care workers(HCWs)). Nevertheless, previous seroprevalence studies focussed on the general population or HCWs in hosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…35 36 A study of primary healthcare providers in the region of Flanders revealed the same trend: here, the seroprevalence remained stable between June and September (around 5%) and increased substantially thereafter (up to 13% in December). 37 The consistently higher estimates in our study compared with the general population confirm the occupational risk for SARS-CoV-2 infection among HCW. Nevertheless, the difference between HCW and the general population (about 4%) was smaller than we had expected and did not increase over time, which suggests that HCW in Belgian hospitals managed to implement relatively adequate personal protection measures.…”
Section: Discussionsupporting
confidence: 71%
“…35 36 A study of primary healthcare providers in the region of Flanders revealed the same trend: here, the seroprevalence remained stable between June and September (around 5%) and increased substantially thereafter (up to 13% in December). 37 The consistently higher estimates in our study compared with the general population confirm the occupational risk for SARS-CoV-2 infection among HCW. Nevertheless, the difference between HCW and the general population (about 4%) was smaller than we had expected and did not increase over time, which suggests that HCW in Belgian hospitals managed to implement relatively adequate personal protection measures.…”
Section: Discussionsupporting
confidence: 71%
“…This is suggested by the lower seroprevalence in this study for PHCPs in Flanders compared to that in an earlier prospective cohort study using dried blood spots analysed in the lab. 25 Not finding a higher seroprevalence among PHCPs, generally concerned about being at high risk of COVID-19 infections, compared to the general population might be explained by the availability and proper usage of personal protective equipment (PPE). 25 Most PHCPs in our study (94.49%) received a first vaccine dose in the period January -March explaining the increase in seroprevalence to 84.1% in April 2021.…”
Section: Discussionmentioning
confidence: 99%
“…25 Not finding a higher seroprevalence among PHCPs, generally concerned about being at high risk of COVID-19 infections, compared to the general population might be explained by the availability and proper usage of personal protective equipment (PPE). 25 Most PHCPs in our study (94.49%) received a first vaccine dose in the period January -March explaining the increase in seroprevalence to 84.1% in April 2021. The monthly incidence of antibodies due to natural infection in those not yet vaccinated in the same time period was estimated to be around 4% in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations